Origins and drivers of crop phenotyping - Pieruschka, Roland (Burleigh Dodds Series in Agricultural Science, 2022)
Plant phenotyping has seen rapid recent development in methods and technologies. This chapter outlines how plant phenotyping has developed over recent decades, driven by factors such as advances in optical sensors, image analysis and automation as well as multidisciplinary cooperation in establishing facilities for high throughput plant phenotyping. The chapter describes successful uses of plant phenotyping and stresses the importance of collaboration in further development, particularly to address emerging potential bottlenecks such as management of data to enable interoperability. It highlights the development of networks across centres and why plant phenotyping will always require multi-disciplinary and multi-site resources and expertise to improve the knowledge about plant-environment interactions.